M3 Patterns of breathlessness in the UK: results from the british lung foundation online breath test. (December 2018) - Elbehairy, AF; Quint, JK; Rogers, J; Laffan, MJ; Polkey, MI; Hopkinson, NS
Abstract : Background: Breathlessness is a common symptom, present in around 10% of older people in the UK. There is concern that this symptom is often dismissed as a normal part of aging, leading to late presentation. The British Lung Foundation (BLF) Online Breath Test provides an opportunity to elucidate the relationship between symptoms, socio-behavioural factors and healthcare seeking behaviour. Methods: Social media was used to encourage members of the public to complete an online breath test developed by the BLF. This included 10 simple questions about demographics, physical activity, smoking history and Medical Research Council (MRC) dyspnoea scale ' https://breathtest.blf.org.uk/ '. Results: 3 65 043 responses were received; 3 56 799 were included in the current analysis after excluding those with missing or wrong data entry. Overall characteristics: 54% aged between 50 and 69 years, 18% were current smokers, 68% had body mass index (BMI) ≥25 kg/m 2 and 35% reported not taking at least 20 min of physical activity a day. 20% of the population reported limiting breathlessness (MRC score of 3 to 5); of these, 85% said they worry about this symptom. 32% of the MRC 3–5 group had not sought medical advice. Of those who had, 58% reported that they had not found the advice helpful (figure 1). Factors associated with increased breathlessness were smoking (r=0.36, p<0.001), age of more than 60 years (r=0.35, p<0.001), physical inactivity (r=0.32, p<0.001) and high body mass index (r=0.25, p<0.001). Conclusions: Data from this large survey suggest that there is considerable unmet need associated with breathlessness in the UK. Although the population is self-selected (they chose to take an online survey), a substantial proportion with limiting breathlessness had not sought medical advice and a substantial proportion of those who had, reported that they had not found it helpful.